2014
DOI: 10.1111/1471-0528.13144
|View full text |Cite
|
Sign up to set email alerts
|

Muscarinic‐mediated vasoconstriction in human, rat and sheep umbilical cords and related vasoconstriction mechanisms

Abstract: Objective The umbilical cord provides nutrition and oxygen to the fetus. The aim of this study was to determine the effects of acetylcholine (ACh) on umbilical cords from humans and other mammals, and the mechanisms of ACh-mediated vasoconstriction in the human umbilical cord.Design Human and animal umbilical cords used in vascular and cellular experiments.Setting Institute for Fetology, First Hospital of Soochow University, Suzhou, China.Population A total of 85 pregnant women, 16 Sprague Dawley rats and seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 28 publications
1
19
0
Order By: Relevance
“…Rings of human, sheep, and rat vessels were prepared, and functional vessel experiments were performed as described [30]. Acetylcholine (10 −4 mol/L) was used for vessel relaxation experiments after application of 5-HT (10 −5 mol/L) or AII (10 −5 mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…Rings of human, sheep, and rat vessels were prepared, and functional vessel experiments were performed as described [30]. Acetylcholine (10 −4 mol/L) was used for vessel relaxation experiments after application of 5-HT (10 −5 mol/L) or AII (10 −5 mol/L).…”
Section: Methodsmentioning
confidence: 99%
“…Following previous reports on ACh-mediated umbilical vaso-constriction in human [28], recently, our team not only provided additional new evidence regarding ACh’s effects on human umbilical arteries and veins, but also found that ACh-induced umbilical contraction in rats and sheep [7], as the first time to demonstrate ACh-mediated umbilical vasoconstrictions in various animals. The present study extended the study and was the first to show that ACh could reliably cause contraction in umbilical vessels in rabbits too.…”
Section: Discussionmentioning
confidence: 64%
“…Based on the finding of ACh-stimulated vasoconstrictions in human, rats, sheep, and rabbits, we would like to propose that blood vessels in umbilical cords have special characters to cholinergic signals, which are very different from healthy blood vessels in other parts of the body where ACh-mediated vasorelaxation was shown. In our experiments during last 6 years, we tested at least one thousand umbilical vessels rings in various species, and observed reliable and repeatable ACh-induced vasoconstriction instead of vasorelaxation [7]. Thus, the accumulated evidence convinces us that it is reasonable to make conclusions now, that the main pharmacological effect of ACh on umbilical blood vessels is to cause vasoconstrictions, no matter in human or animals.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations